320-Row Detector Dynamic 4D-CTA for the Assessment of Brain and Spinal Cord Vascular Shunting Malformations: A Technical Note. Issue 6 (December 2014) - D'Orazio, Federico; Splendiani, Alessandra; Gallucci, Massimo
Shunting vascular malformations of the brain and spinal cord are traditionally studied using digital subtraction angiography (DSA), the current gold standard imaging method routinely used because of its favourable combination in terms of spatial and temporal resolution. Because DSA is relatively expensive, time-consuming and carries a risk of silent embolic events and a small risk of transient or permanent neurologic deterioration, a non-invasive alternative angiographic method is of interest. New 320 row-detector CT scanners allow volumetric imaging of the whole brain with temporal resolution up to ≅ 3 Hz. Those characteristics make computed tomography angiography (CTA) an affordable imaging method to study the haemodynamics of the whole brain and can also be applied to the study of limited portions of the spinal cord. The aim of this paper is to make a brief summary of our experience in studying shunting vascular malformation of the brain and spinal cord using dynamic 4D-CTA, explaining the technical details of the studies performed at our institution, and the state-of-the-art major advantages and drawbacks of this new technique. We found that dynamic 4D-CTA is able to depict the main architectural characteristics of previously untreated vascular shunting malformations both in brain and spinal cord (i.e. their main arterial feeders and draining veins) allowing their correct diagnosis and exhaustive classification, limiting the use of DSA for therapeutic purposes.